The effect of secondary electrons on emission - Li, Yuan (2013)
The effect of secondary electrons on emission is studied by modelling the electrons behaviours in multi-layers, including electron injection, transportation, multiplication, and emission. The dielectric constant model and carrier mobility model are presented to describe the voltage distribution in multi-layers for the non-current injection and current injection respectively. After injection, the electrons are accelerated in SiO2, where they collide with the electrons, generating secondary electrons, consequently contributing to emission. A multiplying factor M is introduced to describe the secondary electrons multiplication in certain electrical field strength. The prediction was further proved by comparing two groups of devices with and without the accelerating layer: ITO/MEH-PPV/SiO2/Al and ITO/MEH-PPV/BCP/Al. The current avalanche observed in current–illumination experiment is a proof of the existence and contribution of secondary electrons.